The role of culture in firm-bank matching - Accetturo, Antonio; Barboni, Giorgia; Cascarano, Michele; Garcia-Appendini, Emilia (Journal of Financial Intermediation, 2023)
We assemble a unique dataset containing population-level information on loan applications in a region hosting two cultural groups to study the role of culture in firm borrowing decisions. We find that firms are more likely to apply for loans from culturally close banks. This effect is stronger for opaque firms, but not for less performing firms, indicating that firms do not expect preferential treatment from same-culture banks. Loan applications to culturally distant banks increase sharply with firms’ size and age, suggesting a role of information asymmetry in firm-bank matching. In contrast, we find no effect of cultural proximity on loan supply. Overall, our results show that demand-side factors play a key role in the formation of same-culture lending relationships.